Clinicopathological Study of Supraglottic Laryngeal Malignancies - Kazi, Md Milon; Hossen, Md Iqbal; Jonaed, Fazle Elahi; Roktim, IM Hashim Reza; Elahi, Mirza Kaisar; Chowdhury, M Alamgir (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Laryngeal malignancy is the second most common malignancy in head neck region worldwide. Incidence of supraglottic carcinoma is more common in this country which interferes with most vital functions in the sufferers like voice, respiration and swallowing by virtue of its anatomical location, local infiltration and direct extension. Objectives: To find out the clinicopathological profile of supraglottic laryngeal malignancies of the patients attending in a tertiary level Hospital. Methods: A cross sectional study was conducted among seventy eight cases of supraglottic carcinoma who were histopathologically proven selected from the in-patient department of ENT and Head -Neck Surgery Dhaka Medical College Hospital, Dhaka during January 2020 to July 2021. Results: Among 78 cases in this study, male: female ratio 10.1:1 and mean age was 52.1 (± 4.6) years with the range from 40 to 78 years. Majority of the patients came from low socioeconomic condition (79.5%). Regarding habit 93.6% of cases were smoker and 59% are habituated in chewing betel nut and leaves, 3.8% were with chewing tobacco and alcohol 2.6%. Most of patients presented with more than one symptom and the commonest was change of voice (87.2%), which followed by dysphagia (78.2%), neck swelling (55.1%), irritable cough (32%) and dyspnoea (20.5%). A big portion of the patients (39.7%) had T2 lesion followed by T3 lesion (38.5%), T1 lesion (11.5%) and T4 lesion (10.3%) clinically. Clinical nodal involvement presented in 55.1% cases and there was no distance metastasis. 56 (71.8%) patients had exophytic growth and 22 (28.2%) patients had ulcerative growth. A large portion of the patients (65.4%) had growth in Aryepiglottic fold followed by False Cord (34.6%), arytenoid (29.5%) and Epiglottis (25.6%). On histopathological evaluation, Squamous cell carcinoma (SCC) was present in 85.8% cases, well differentiated (14.1%), moderately differentiated (53.8%), and poorly differentiated (17.9%). While Adenocarcinoma found in 7.7% cases and Non-Hodgkin Lymphoma present in 6.4% cases. Conclusion: Supraglottic carcinoma usually occurs in 5th decade with male predominancy in poor socio economic group. Smoking, chewing (tobacco and betel nut) habits and alcohol consumption have got strong relation in the causation of supraglottic carcinoma.More than half of the cases has nodal metastasis and predominant histological type was squamous cell carcinoma. Bangladesh J Otorhinolaryngol 2022; 28(2): 141-148